Application of low-field nuclear magnetic resonance to assess the onset of asphaltene precipitation in petroleum. (1st April 2020) - Morgan, Vinícius G.; Bastos, Thabita M.; Sad, Cristina M.S.; Leite, Juliete S.D.; Castro, Eustáquio R.V.; Barbosa, Lúcio L.
Highlights: Low field NMR allowed detect the asphaltene precipitation. The precipitation onset changed between 0.931 and 2.759 mL g −1 . Abstract: Knowledge of the onset of the asphaltene precipitation point is important in preventing pipe clogging and the reduction of productivity. In this study, we propose a new and simple strategy to determine the onset point of asphaltene precipitation by a low-field nuclear magnetic resonance (NMR) technique based on transverse relaxation time (T2 ) measurements. Six Brazilian crude oil (light, medium, and heavy) samples, with asphaltene contents ranging from 0.10 to 7.10 wt%, were assessed using n-heptane as the precipitant, according to the ASTM D6560 method. The good correlation between T2 and the n-heptane/oil ratio indicated the onset precipitation values between 0.931 and 2.759 mL g −1 . NMR results shows agreement with optical microscopy and literature results. We also propose a correlation between asphaltene content and onset of the asphaltene precipitation. This new idea expand the applicability of low-field NMR in crude oil studies, providing an alternative method for asphaltene precipitation under laboratory conditions and opens the possibility to quantifying the asphaltene content in crude oil without the laborious standard ASTM method.